Race differences in prevalence of chronic kidney disease among young adults using creatinine-based glomerular filtration rate-estimating equations - Peralta, Carmen A. (Oxford University Press, 2010)
Background. Despite a higher incidence of end-stage renal disease (stage 5), blacks have been shown to have the same or lower prevalence of chronic kidney disease (CKD stages 3 and 4). Current creatinine-based glomerular filtration rate (GFR)-estimating equations may misclassify young, healthy blacks. Methods. Among 3501 young adults (mean age 45), we compared the prevalence of CKD in blacks and whites using the Modification of Diet in Renal Disease (MDRD) and the CKD Epidemiology Collaboration (CKD-EPI) equations. In addition, we used measured creatinine excretion rates to determine the actual excretion ratio for CARDIA (race coefficient 12%) and applied this to the CKD-EPI equation. We also studied the prevalence of CKD risk factors among black and white participants near the CKD threshold cut-off (eGFR CKD-EPI 60–80 mL/min/1.73 m(2)) to estimate the relative likelihood of misclassification in blacks and whites. Results. Using the MDRD equation, prevalence of CKD stages 4 and 5 was higher for blacks compared with whites (0.6% vs. 0.1%, P-value 0.05). In contrast, prevalence of eGFR <60 mL/min/1.73 m(2) was significantly higher for whites (3.6%) compared with blacks (1.9%), due to higher prevalence of stage 3 among whites. Prevalence of CKD was similar for blacks and whites using CKD-EPI equation (1.2%), but was higher among blacks when using the CARDIA-derived race coefficient (1.6% vs.1.2%, P-value = 0.03). Among persons with eGFR by CKD-EPI of 60–80 mL/min/1.73 m(2), blacks had higher levels of albuminuria, uric acid, systolic blood pressure and higher diabetes prevalence. Conclusions. CKD classification among young blacks is very sensitive to the race coefficients. Despite whites having higher rates of CKD stage 3, blacks with eGFRs just above the CKD threshold had higher rates of CKD risk factors. Current equations used to define CKD may systematically miss a high-risk group of blacks at a time in the disease course when interventions are crucial.